TI_GERICHTE 12.2009.191 vom 2. Juli 2010 , Mandato, obbligo di rendiconto della banca, precetto esecutivo civile - TI Tribunale d'appello (2010)
Mandato, obbligo di rendiconto della banca, precetto esecutivo civile